Breaking bad. The complete second season - Cranston, Bryan, 1956-; Gunn, Anna, 1968-; Paul, Aaron, 1979-; Norris, Dean.; Mitte, R. J.; Brandt, Betsy; Johnson, Mark, 1945 December 27-; Gilligan, Vince; Sony Pictures Television; Sony Pictures Home Entertainment (Firm); American Movie Classics Company ([United States] : Sony Pictures Home Entertainment, 2010)
After an unremarkable chemistry teacher learns he has terminal cancer, he turns to an exciting life of crime to provide for his loved ones.
Disc 1.Seven Thirty-Seven ;Grilled ;Bit By a Dead Bee ;Down -- disc 2.Breakage ;Peekaboo ;Negro Y Azul -- disc 3.Better Call Saul ;4 Days Out ;Over -- Disc 4.Mandala ;Phoenix ;ABQ.
Contains thirteen episodes of the second season.
Bonus features: commentaries; deleted scenes; featurettes; music video; gag reel.
Bryan Cranston, Aaron Paul, Anna Gunn, RJ Mitte, Dean Norris, Betsy Brandt.
DVD release of episodes originally broadcast on AMC in 2009.
Not rated.
DVD ; anamorphic widescreen (1.85:1) presentation ; Dolby digital 5.1 surround.
Keywords: Chemistry teachers -- Drama; Drug dealers -- Drama; Chemistry -- Drama; Criminal behavior -- Drama; Drug traffic -- Drama; Terminally ill -- Drama; Crime -- Drama; Cancer -- Patients -- Drama; Methamphetamine -- Economic aspects -- Drama; Drug dealers -- Family relationships -- Drama; Ice (Drug) -- Drama; Television crime shows; Fiction television programs; Television programs for the hearing impaired